1985
DOI: 10.1128/jb.161.3.913-920.1985
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning in Escherichia coli of Erwinia chrysanthemi genes encoding multiple forms of pectate lyase

Abstract: The phytopathogenic enterobacterium Erwinia chrysanthemi excretes multiple isozymes of the plant tissue-disintegrating enzyme, pectate lyase (PL). Genes encoding PL were cloned from E. chrysanthemi CUCPB 1237 into Escherichia coli HB101 by inserting Sau3A-generated DNA fragments into the BamHI site of pBR322 and then screening recombinant transformants for the ability to sink into pectate semisolid agar. Restriction mapping of the cloned DNA in eight pectolytic transformants revealed overlapping portions of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…1B) with a molecular size of 30.5 kDa could sometimes be detected in S. citri by SDS-PAGE, especially when spiralin was purified by immunoaffinity chromatography before electrophoresis. The on July 16, 2020 by guest http://jb.asm.org/ Downloaded from various forms of spiralin, ranging from 30.5 to 28.0 kDa, might represent a variety of postranslational modifications as has been suggested for the pectate lyase gene of Erwinia chrysanthemi cloned and expressed in E. coli (6). Knowing that spiralin is a membrane protein, it is tempting to envisage the minor spiralin form (30.5 kDa) in S. citri as a prespiralin containing a polypeptidic extension which may be a signal sequence equivalent to that demonstrated for bacterial and eucaryotic membrane proteins (25).…”
Section: Discussionmentioning
confidence: 95%
“…1B) with a molecular size of 30.5 kDa could sometimes be detected in S. citri by SDS-PAGE, especially when spiralin was purified by immunoaffinity chromatography before electrophoresis. The on July 16, 2020 by guest http://jb.asm.org/ Downloaded from various forms of spiralin, ranging from 30.5 to 28.0 kDa, might represent a variety of postranslational modifications as has been suggested for the pectate lyase gene of Erwinia chrysanthemi cloned and expressed in E. coli (6). Knowing that spiralin is a membrane protein, it is tempting to envisage the minor spiralin form (30.5 kDa) in S. citri as a prespiralin containing a polypeptidic extension which may be a signal sequence equivalent to that demonstrated for bacterial and eucaryotic membrane proteins (25).…”
Section: Discussionmentioning
confidence: 95%
“…Several genes encoding depolymerizing pectic enzymes have been cloned in Escherichia coli, mainly from plant-pathogenic species of Erwinia and Pseudomonas. These studies, together with the isolation of mutants Condemine et al 1986), have provided considerable information about their chromosomal organization (Reverchon et al 1986;Plastow 1988;Tamaki et al 1988), structure (Tamaki et al 1988;He and Colmer 1990;Spok et al 1991), regulation (Keen et al 1984;Zink and Chatterjee 1985), role in phytopathogenicity (Collmer et al 1985;Lei et al 1988) and evolutionary relationships by sequence comparisons (Tamaki et al 1988;Liao 1991).…”
mentioning
confidence: 99%
“…Molecular and in vivo cloning experiments have revealed that E. chrysanthemi strains contain up to five pel genes encoding PL isozymes with isoelectric points that are acidic (pelA), near neutral (pelB and peiC), or alkaline (pelD and pelE) (7,11,14,24,34). Although the pel genes are contained in two clusters on the E. chrysanthemi chromosome (pelA-pelE-pelD and pelB-pelC), they all appear to be expressed from separate promoters (12,15,31).…”
mentioning
confidence: 99%
“…The pelB and pelE genes of strain EC16 have been sequenced and reveal no homology (12). E. coli clones containing E. chrysanthemi or E. carotovora pel genes expressed from their native promoters cause limited maceration but only if very high levels of inoculum (typically 107 cells per inoculation) are used (7,11,28). E. chrysanthemi mutants deficient in either pelB or pelC are unaltered in virulence as determined by quantitative maceration assays (29,30).…”
mentioning
confidence: 99%